Conversations with Chester - Mallari, Eulan Andrei C.; Palileo, Shirley (Quezon City University of the Philippines Diliman, 2024)
Conversations With Chester is a narrative short film about healing through self-perseverance. It follows Chester, an average worker going home from his graveyard shift, having conversations with the community cat, also named Chester. He packs his things to move out the following day. But as he keeps procrastinating, he reminisces on the last conversations he had with his ex-boyfriend Drew, who he shared the apartment with, and how their relationship was bound to never last as they wanted different things in life.

This production thesis uses a narrative story-telling format, as well as flashbacks as a narrative technique. This film thesis also makes use of two original songs that open and close the film, detailing the emotional journey of the character. The study is grounded on the theory of proxemics and semiotics to explain the role of the cinematic space with the character’s inner thoughts, and the theory of emotion regulation to visualize the character’s processing of emotions.
Thesis
Keywords: Conversations with Chester (Short film)